Factors affecting the performance of village equipment - Suswati Nasution; Ahmad Soleh; Iwa Pala (Business and Entrepreneurial Review, 2022)
In the government order, honest, open, responsible, and democratic government behavior is needed, while in the community order it is necessary to develop mechanisms that provide opportunities for community participation in the decision-making process for the common good. Employee performance is very necessary for achieving good governance. The purpose of this study was to determine the factors that influence the performance of village officials, namely leadership, motivation, and work environment in Talo District, Seluma Regency. The sample in this study was 107 village officials in Talo District, Seluma Regency. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test, and hypothesis testing. The results showed that leadership, motivation, and work environment had a significant influence on performance either partially or simultaneously.